Analisis Sistem Pengendalian Intern Atas Penerimaan Kas: Pada PT BPR Angsa Sedanayoga - Dwitayanti, Cok Putri; Yuniasih, Ni Wayan; Andayani W, Rai Dwi (Hita Akuntansi dan Keuangan, 2024)
BPR Angsa Sedanayoga (BAS Bank) is a people’s credit bank that was established on August 9, 1993 which is located at Jalan Raya Batubulan no. 168 Sukawati, Gianyar and already has a cash office on the Ground Floor of Kiosk No. 19 Gianyar People’s Market. The purpose of this study is to describe the cash receipts internal control system at PT BPR Angsa Sedanayoga which has been running so far. This research is a qualitative research, with data collection techniques in the form of observation, interviews and documentation. The results showed that the internal control system applied to BPR Angsa Sedanayoga (BAS Bank) had not gone well, not in accordance with the elements contained in the theory of cash receipts internal control. This is proven by the double function of cash receipts due to the limited number of employees so that internal control is not effective. Keywords: Internal Control, Cash Receipt, Financial Planning, Division of Responsibilities